TRENDS AND RESEARCH PATTERNS IN THE DEVELOPMENT OF RURAL TOURISM IN INDONESIA: A SYSTEMATIC LITERATURE ANALYSIS - Mukti, Ari; Fadlurrahman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study explores trends and research patterns related to the development of tourism villages in Indonesia through a Systematic Literature Review (SLR) approach guided by the PRISMA method. Focusing on the 2022–2024 period, the research maps out key themes, research methods, and stakeholder involvement. An analysis of 153 articles reveals the dominance of qualitative methods aimed at exploring local social and cultural contexts, with research distribution heavily concentrated in Central Java, West Java, and Bali. While these methods provide in-depth insights, the lack of quantitative studies creates a gap in providing measurable data. Furthermore, stakeholder involvement indicates limited participation from the private sector, higher education institutions, and media. Dominant research topics include development management, community engagement, and multi-stakeholder collaboration. The findings highlight the need for research in marketing, digital innovation, and the impacts of development. Additionally, the study underscores the importance of diversifying research methods, conducting studies outside Java and Bali, and fostering cross-sector collaboration to support the sustainability of tourism villages. This research provides an academic foundation to inform policymaking and identifies open research opportunities in the field of tourism village development